MODELING THE EFFECT OF IMMUNOSUPPRESSANTS ON THE TRANSMISSION DYNAMICS OF HEPATITIS C VIRUS AFTER LIVER TRANSPLANTATION - Ismail, Seleman (IJRDO -JOURNAL OF MATHEMATICS, 2019)
Hepatitis C virus (HCV) infection is a principal source of chronic HCV infection and cirrhotic hepatitis worldwide, which needs liver transplantation (LT). But LT, being a therapeutic option for cirrhosis, has not guaranteed complete extermination of the disease. In this paper, we formulated deterministic mathematical model to study the effect of immunosuppressants on the transmission dynamics of recurrent HCV after LT. We established the existence of disease free equilibrium,  and so derived the basic reproductive number, . We also computed sensitivity indices of pertaining to some model parameters and  found  that  the natural death rate of graft hepatocytes,  is the most sensitive parameter; followed by the parameters  ,  and  for the infection rate , virus production rate and recruitment  rate of new susceptible hepatocytes respectively, while the disease-induced death rate,  is the least negatively sensitive parameter. Besides, we performed numerical simulations and found that the results are consistent with the analytical results. Thus, we recommend that deliberate control measures should be directed to a HCV-infected transplant recipient who is incapable of clearing the virus spontaneously so as to reduce recurrent HCV transmission, or exterminate it, by targeting the most sensitive parameters with guaranteed non-rejection of the liver transplant by the recipient body immune response